2019
DOI: 10.3390/molecules24061136
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Diversity in Rhizomes of Three Reynoutria Species and their Antioxidant Activity Correlations Elucidated by LC-ESI-MS/MS Analysis

Abstract: The rhizome of Reynoutria japonica is a well-known traditional herb (Hu zhang) used in East Asia to treat various inflammatory diseases, infections, skin diseases, scald, and hyperlipidemia. It is also one of the richest natural sources of resveratrol. Although, it has been recently included in the European Pharmacopoeia, in Europe it is still an untapped resource. Some of the therapeutic effects are likely to be influenced by its antioxidant properties and this in turn is frequently associated with a high sti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 62 publications
7
76
0
Order By: Relevance
“…In the peak [R48] , a flavan-3-ol polymer was detected: it was observed as a precursor ion [M-H] − at m / z 729.1455, generating in MS 2 experiment major product ions at m / z 577 ([M-H-152] − , loss of a galloyl group), m / z 441 ([M-H-288] − , loss of an (epi)catechin unit), m / z 407 ([M-H-152-18] − , resulting from RDA fragmentation and water elimination or loss of a galloyl group and water), and m / z 289 ([M-H-441] − , loss of an (epi)catechin gallate moiety). These MS data were in accordance with the literature [45,47,48], and consequently, this compound in peak [R48] was assigned to a procyanidin dimer monogallate.…”
Section: Resultssupporting
confidence: 88%
“…In the peak [R48] , a flavan-3-ol polymer was detected: it was observed as a precursor ion [M-H] − at m / z 729.1455, generating in MS 2 experiment major product ions at m / z 577 ([M-H-152] − , loss of a galloyl group), m / z 441 ([M-H-288] − , loss of an (epi)catechin unit), m / z 407 ([M-H-152-18] − , resulting from RDA fragmentation and water elimination or loss of a galloyl group and water), and m / z 289 ([M-H-441] − , loss of an (epi)catechin gallate moiety). These MS data were in accordance with the literature [45,47,48], and consequently, this compound in peak [R48] was assigned to a procyanidin dimer monogallate.…”
Section: Resultssupporting
confidence: 88%
“…Recently, we tentatively identified flavan-3-ols and B-type proanthocyanidins from monomers up to decamers (monomers-flavan-3-ols, dimers, trimers, tetramers, pentamers, hexamers, heptamers, octamers, nonamers and decamers) and some of their gallates (monomer gallates, dimer gallate, dimer digallates, trimer gallates, tetramer gallates, pentamer gallates, hexamer gallates) in Japanese knotweed rhizomes [12,13]. Other authors reported identification of monomers [8,9,[14][15][16], monomer gallates [8,14,16], dimers [8,9,15], dimer gallates [15,16] dimer digallates [15,16] trimers [15], trimer gallates [15] trimer digallates [15] tetramer [15], tetramer gallates [15], pentamers [15], heptamers [15] and octamers [15] in rhizomes of Japanese [8,9,[14][15][16], Bohemian [14,15] and giant knotweed [8,9,[14][15][16]. However, only monomers [8,9], monomer gallates [8,9], dimers [8,9], dimer gallates [8,…”
Section: Introductionmentioning
confidence: 99%
“…Another described class of polyphenolic compounds belonging to hydrolyzed tannins were sanguiins. Among the 9 identified compounds, only 4 had earlier been detected in S. officinalis L. as sanguiin H-6 (11,89; m/z 1870), sanguiin H-4 (41; m/z 633), and sanguiin H-10 isomer (48; m/z 783) by Karkanis et al [3] and Zhu et al [2], whereas the other 5 were never identified, as shown by literature data. Therefore, based on the primary peak at m/z 785 and MS/MS fragmentation peaks at m/z 633 and 301, and due to the loss of 152 and 332 Da groups, compounds No.…”
Section: Introductionmentioning
confidence: 86%
“…Additionally, fragments were noted at m/z 169 and at m/z 301 formed through lactonization of the characteristic hexahydroxydiphenoyl group to ellagic acid. These compounds comprise typical galloyl and HHDP groups, respectively, which have earlier been described in the available literature [1][2][3][9][10][11]. Furthermore, if ellagitannin or galloyl derivates are composed of one or a few galloyl groups taking part in sugar synthesis, the fragmentary ion first discards a molecule of gallic acid and then a galloyl group or groups during fragmentation [10].…”
Section: Introductionmentioning
confidence: 97%